Religious hate speech, libertà di religione e libertà di espressione. Intersezioni tra forma e sostanza dei diritti nella società multiculturale (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. Premesse - 2. Un possibile modello alternativo di tutela: la forma della tutela - 3. Un possibile modello alternativo di tutela: la sostanza della tutela - 4. Alcuni casi pratici - 4.1. Il leader politico - 4.2. Il leader religioso - 5. Conclusioni.Religious hate speech, freedom of religion and freedom of expression. Reshaping the rights in the multicultural societiesABSTRACT: In the multicultural societies, lawyers are more and more often engaged in identifing useful tools to solve the rising conflicts between fundamental rights. The exercise of freedom of religion and freedom of expression can led into this kind of phenomena that could be taken into consideration by law, like hate speech and religious hate speech. The paper tries to approach two particular form of hate speech, the political and the religious one, to check if some alternative models of protection could be implemented to assure an effective protection of minorities without any sacrifice of individual fundamental rights.